ANALISIS YURIDIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 46/PUU-VIII/2010 TENTANG STATUS ANAK DI LUAR PERKAWINAN SEBAGAI DASAR PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA HAK WARIS ANAK DI LUAR PERKAWINAN - Maria Widiastuti; Adnyani, Ni Ketut Sari; landrawan, i wayan (Jurnal Ilmu Hukum Sui Generis, 2024)
This research aims to find out: (1) the basic considerations of Constitutional Court Judges in deciding on children's inheritance rights for children outside of marriage. (2) the difference between the legal inheritance rights of children in marriage and the inheritance rights of illegitimate children in marriage. (3) the relevance of the Constitutional Court decision Number 46/PUU-VIII/2010 concerning the Status of Children Outside of Marriage which is used as a reference by Judges to decide cases regarding the inheritance rights of children outside of marriage. (4) legal reconstruction that can be accommodated by judges into marriage law regarding the Constitutional Court decision Number 46/PUU-VIII/2010 concerning the Status of Children Outside of Marriage. The type of research used by researchers is normative legal research, namely through a statutory and regulatory approach and a conceptual approach. The sources of legal material used are the 1945 Constitution, the Civil Code, Customary Law, and Constitutional Court Decisions. The research results show that (1) The legal force of the Constitutional Court's decision is binding and every child has the right to all forms of protection. (2) There are differences in the inheritance rights of legitimate children and illegitimate children in marriage. (3) The relevance of the decision of the Constitutional Court Number 46/PUU-VIII/2010 concerning the Status of Children Out of Wedlock reflects the principle of equality before the law, which confirms that everyone has the right to recognition, guarantees and protection. , and fair legal certainty and equal treatment before the law. (4) In the Constitutional Court Decision Number 46/PUU-VIII/2010 concerning the Status of Children outside of marriage, Judges can use science and technology to determine the status of the father of a child outside of marriage.